Magnetic sensor utilizing fabry pérot setup. - Teh, Ezekiel Zhi Wen. (2011)
Magnetic Fluid has superparamagentic property; it has high susceptibility to magnetic field, and yet has the ability to lose that magnetization when the external magnetic field is removed. Hence, it has the potential to be used as a magnetic field sensing element. In combination with the highly sensitivity Fabry-Pérot setup, we investigate the possibility to create a high sensitivity magnetic sensor. In our reflective index experiment, we are able to characterize variation in reflective index as magnetic field is applied to the sensor. The sensitivity of the sensor can be easily adjusted by varying the Fabry Pérot cavity length. A smaller cavity,10um, length will create sensor with higher respond to low magnetic field, but with lower precision as the phase shift has a smaller gradient as opposed to a 40um gap. A wider cavity produce lower respond to low magnetic field, but it has a larger gradient in term of wavelength phase shift. The temperature stability of the sensor is influenced by the thermal expansion of the sensor head, and the variation could reach 2.34nm phase at 65 degree Celsius. Hence, thermal compensation need to be addressed should the 10um gap sensor is used for sensing.